Cuantificación de flavonoides totales de las inflorescencias de bejaria aestuans l. “purum rosa” procedentes de la provincia de Otuzco – La Libertad - Reyes Avalos, Elder Miler (2012)
Flavonoids, large group of secondary metabolites have diverse functions in plants and makes them responsible for important pharmacological effects. Bejaria aestuans L. known as "purum rosa", grows in the highlands of the department of La Libertad and is popularly used in the treatment of some types of infections. They were attached to the genin flavónicas so. This paper poses the following problem: What is the concentration of total flavonoids in the inflorescences of Bejaria aestuans L. "Purum rosa"? As the main objective Extraction and quantification of total flavonoids, expressed as quercetin from the inflorescences of Bejaria aestuans L. "Purum rosa." The sample was collected in the village of Capachique, Usquil district, Otuzco province, La Libertad region in March 2012. The method used was that described by Kostennikova Z (1983), amended by the chair of Pharmacognosy, Faculty of Pharmacy and Biochemistry, National University of Trujillo. In which the flavonoids is extracted by Soxhlet method and by hydrolysis separates the genin of sugars and purifies them according to their solubility in ethanol. Then read on UV-Vis spectrophotometer at 258 nm. We obtained aconcentration of 0.9265% ± 0.00917% of total flavonoids expressed as quercetin from the inflorescences of Bejaria aestuans L. (purum rosa), with this concentration within the ranges found in other genera of the same family